PEDOT:PSS‐Coated Stimulation Electrodes Attenuate Irreversible Electrochemical Events and Reduce Cell Electropermeabilization. Issue 19 (9th September 2021) - Dijk, Gerwin; Ruigrok, Hermanus J.; O'Connor, Rodney P.
Abstract: Electroporation or electropermeabilization occurs when cells are exposed to sufficiently high‐pulsed electric fields. This phenomenon is now an important technique to facilitate the transmembrane transport of molecules, however, the role of the electrode material and associated electrochemical events remain unclear. Here, it is shown that electrical stimulation with PEDOT:PSS‐coated electrodes strongly reduces irreversible electrochemical reactions that otherwise lead to changes in pH and the generation of reactive oxygen species. Coated electrodes exhibit a slightly higher threshold for cell stimulation, however, little electropermeabilization is observed at voltages that greatly exceed the threshold for uncoated electrodes. The findings indicate that electrically induced, extracellular chemical changes represent an important mechanism in the cellular electropermeabilization response. Moreover, PEDOT:PSS‐coated electrodes separate the delivery of electric pulses from chemical changes, which paves the way for future experiments that could lead to a better understanding of underlying mechanisms. Abstract : Pulsed electrical stimulation with sufficiently high voltages can initiate irreversible electrochemical reactions which affect the cellular response. This work characterizes the charge injection, pH changes, generation of reactive oxygen species, and cell permeabilization of PEDOT:PSS‐coated stimulation electrodes and compares the performance with uncoated electrodes.